Parental occupational exposure to pesticides and the risk of childhood leukemia in Costa Rica - Monge, Patricia; Wesseling, Catharina; Guardado, Jorge; Lundberg, Ingvar; Ahlbom, Anders; Cantor, Kenneth P; Weiderpass, Elisabete; Partanen, Timo (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'Parental exposure to pesticides and the risk of leukemia in offspring were examined in a population-based case–control study in Costa Rica. ' ' METHODS ': 'All cases of childhood leukemia (N=334), in 1995–2000, were identified at the Cancer Registry and the Children’s Hospital. Population controls (N=579) were drawn from the National Birth Registry. Interviews of parents were conducted using conventional and icon-based calendar forms. An exposure model was constructed for 25 pesticides in five time periods. ' ' RESULTS ': 'Mothers’ exposures to any pesticides during the year before conception and during the first and second trimesters were associated with the risk [odds ratio (OR) 2.4, 95% confidence interval (95% CI) 1.0–5.9; OR 22, 95% CI 2.8–171.5; OR 4.5, 95% CI 1.4–14.7, respectively] and during anytime (OR 2.2, 95% CI 1.0–4.8). An association was found for fathers’ exposures to any pesticides during the second trimester (OR 1.5, 95% CI 1.0–2.3). An increased risk with respect to organophosphates was found for mothers during the first trimester (OR 3.5, 95% CI 1.0–12.2) and for fathers during the year before conception and the first trimester (OR 1.5, 95% CI 1.0–2.2 and OR 1.6, 95% CI 1.0–2.6, respectively), and benzimidazoles during the first, second, and third trimesters of pregnancy (OR 2.2, 95% CI 1.0–4.4; OR 2.2, 95% CI 1.0–5.0; OR 2.2, 95% CI 1.0–5.2, respectively). There was a suggestion of an exposure–response gradient for fathers as regards picloram, benomyl, and paraquat. Age at diagnosis was positively associated with fathers’ exposures and inversely associated with mothers’ exposures. ' ' CONCLUSIONS ': 'The results suggest that parental exposure to certain pesticides may increase the risk of leukemia in offspring.
Keywords: cancer epidemiology; case–control study; child; childhood cancer; childhood leukemia; Costa Rica; developing country; fetal exposure; parental occupational exposure; pesticide; pregnancy; reproductive effect; risk; tropics